If it's not what You are looking for type in the equation solver your own equation and let us solve it.
((N^12)^4)/3 = 0
(12)^(13)
x^4+4*x^3-x^2-(16*x)-12 = 0
5;6;2;3;0;0
cos(x)*e^x
| (N^12)^4/3 | | a(5a-6b)= | | 1/3r-1/24=0 | | f(x)=-2x^2+2x-7 | | (2x+3)(4+3x)=0 | | 5q/8=3 | | 4+16x+29=0 | | -3cotx=8secx | | 4x+13=29-26xI+26x | | 2sinx(1-4sin^2x)=0 | | 4+6x=10x-32 | | 2sinx(1-4sin^2x)=o | | 1/7=(x-6)/49 | | 4p+11=9 | | 2^3x=1/4 | | 10(s-5)=-94 | | 81=(25x)(x) | | 4a-2a^2=6-4a | | 6(1/2)-1^(2) | | (x+6)(x+6)+1=9x | | (x+6)2+1=9x | | 3(a-7)=6 | | 2*sin(2x)+cos(2x)=1 | | (x-3)(x+3)=3x(x+1)+3x-9 | | 2j+4j= | | 2x+9+y=0 | | 8g-5=51 | | 0.0225+0.04=0 | | 6x+11=24 | | x+(x+5)+(x-2)=75 | | 6(x+3)-8(x-7)=88-9x | | (2y-8)-3(4-3y)=11y-20 |